2015
DOI: 10.1007/s10815-015-0433-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aspects of monomorphic teratozoospermia: a review

Abstract: Teratozoospermia is characterized by the presence of spermatozoa with abnormal morphology over 85 % in sperm. When all the spermatozoa display a unique abnormality, teratozoospermia is said to be monomorphic. Two forms of monomorphic teratozoospermia, representing less than 1 % of male infertility, are recognized: macrozoospermia (also called macrocephalic sperm head syndrome) and globozoospermia (also called round-headed sperm syndrome). Macrozoospermia is defined as the presence of a very high percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 73 publications
0
82
0
3
Order By: Relevance
“…The genetic basis of globozoospermia has been a subject of extensive studies and mainly associated with deletion or deficiency of DPY19L2, SPATA16, Spaca1, and PICK1 genes which are thought to be involved in acrosome biogenesis (Elinati et al, 2012;Fujihara et al, 2012;Chianese et al, 2015;De Braekeleer et al, 2015). In this regard, assessment of RNA in spermatozoa has been recommended as it may reveal the historical record of testicular function and spermatogenesis and thereby can be considered as a genetic fingerprint of the individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic basis of globozoospermia has been a subject of extensive studies and mainly associated with deletion or deficiency of DPY19L2, SPATA16, Spaca1, and PICK1 genes which are thought to be involved in acrosome biogenesis (Elinati et al, 2012;Fujihara et al, 2012;Chianese et al, 2015;De Braekeleer et al, 2015). In this regard, assessment of RNA in spermatozoa has been recommended as it may reveal the historical record of testicular function and spermatogenesis and thereby can be considered as a genetic fingerprint of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Only in one case (G12), the expression levels of these transcripts were close to fertile men, but AOA could not result in a good fertilization rate (17%) in this case. Different explanations can be provided for such a case including defective chromatin packaging or increased DNA fragmentation which has been thought to affect fertilization and pregnancy outcome of ICSI oocytes (De-Braekeleer et al, 2015;Hosseinifar et al, 2015). Yassine et al (2015) recently demonstrated that in globozoospermic mice and humans with deletion of DPY19L2, sperm devoid of an acrosome has altered genomic packaging and increased DNA damage which can compromise ICSI outcomes (Yassine et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…La globozoospermie (spermatozoïdes à tête ronde) est une forme de tératozoospermie monomorphe relativement rare avec une incidence inférieure à 0,1 % chez les hommes infertiles, essentiellement caractérisée par des spermatozoïdes à tête ronde dépourvus d'acrosome 2 . Des mutations ou des délétions dans trois gènes, SPATA16 (spermatogenesis-associated protein 16), PICK1 (qui code une protéine interagissant avec la protéine kinase Cα) et DPY19L2 (dpy-19-like 2), ont été retrouvées chez des patients globozoospermiques [19]. De façon intéressante, PLCζ est absente ou très diminuée dans les spermatozoïdes des patients globozoospermiques porteurs d'une anomalie de DPY19L2 [20].…”
Section: Diagnostic éTiologiqueunclassified
“…It is characterized by the presence of spermatozoa with abnormal morphology in over 85% in sperm (De Braekeleer et al, 2015). These abnormalities may include heads that are large, small, tapered, or pyriform or tails that are abnormally shaped.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Kusz-Zamelczyk et al (2013) were the first to describe the association between NANOS1 gene mutations with human severe oligoasthenoteratozoospermia. Recent reports also suggest that mutations or deletions in AURKC, SPATA16, PICK1, and DPY19L2 are responsible for teratozoospermia (De Braekeleer et al, 2015). However, the genomic or gene expression variation contributing to teratozoospermia is still unknown.…”
Section: Introductionmentioning
confidence: 99%